2015
DOI: 10.1155/2015/798478
|View full text |Cite
|
Sign up to set email alerts
|

Sedative and Analgesic Effects of Entonox Gas Compared with Midazolam and Fentanyl in Synchronized Cardioversion

Abstract: The purpose of this study was to determine if the Entonox gas could cause adequate analgesic and sedative effects in patients who need cardioversion. In this randomized not blinded clinical trial, the sedative and analgesic effects of midazolam and fentanyl were compared with Entonox. Eligible patients who need synchronized cardioversion because of dysrhythmia were randomly divided into two groups. The first group received intravenous midazolam and fentanyl; the second group received Entonox through a blower-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…At analgesic doses, it exhibits cardiovascular stability and no respiratory depression and can provide analgesia on par with systemic opiate administration. 178,182,183,184 The rapid diffusion of N 2 O can lead to accumulation in gas-filled spaces within the body, and it should be used cautiously in head and chest trauma victims so as not to worsen pneumothorax or pneumocephalus, and its use is contraindicated in recently ascended divers. 185 Three important limitations for the use of N 2 O in the austere setting exist.…”
Section: Nitrous Oxidementioning
confidence: 99%
“…At analgesic doses, it exhibits cardiovascular stability and no respiratory depression and can provide analgesia on par with systemic opiate administration. 178,182,183,184 The rapid diffusion of N 2 O can lead to accumulation in gas-filled spaces within the body, and it should be used cautiously in head and chest trauma victims so as not to worsen pneumothorax or pneumocephalus, and its use is contraindicated in recently ascended divers. 185 Three important limitations for the use of N 2 O in the austere setting exist.…”
Section: Nitrous Oxidementioning
confidence: 99%
“…Kalinox has demonstrated its analgesic efficacy and safety in various procedures associated with mild to moderate pain including minor surgery, emergency transportation, venous cannulation, colonoscopy, dentistry, percutaneous liver biopsy or percutaneous renal biopsy [ 7 , 8 , 9 ]. Up to now, the use of Kalinox has not been investigated in coronary interventions with a rarity of data exploring its use during cardioversion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent investigation of Masoumi et al [1], the intravenous association of midazolam and fentanyl was compared to inhaled nitrous oxide in the synchronized cardioversion. This study is very important since several drug schemes have been used for anesthesia during electrical cardioversion, with different mechanism of action, duration, and side effects, but, until now, no technique demonstrated a clear superiority over one another [2].…”
mentioning
confidence: 99%
“…The primary endpoint of Masoumi et al [1] was the degree of pain experienced by the patient, and secondary endpoints were sedation duration, time to full recovery consciousness, and need of additional doses to induce and maintain sedation. After randomization and analysis of 40 patients, this investigation demonstrated that nitrous oxide promoted a better analgesic effect and that it was also associated with shorter sedation duration and time to full recovery consciousness.…”
mentioning
confidence: 99%